Neuropsychiatric correlates of olfactory identification and traumatic brain injury in a sample of impulsive violent offenders - Challakere Ramaswamy, Vasudeva Murthy; Butler, Tony; Ton, Bianca; Wilhelm, Kay; Mitchell, Philip B.; Knight, Lee; Greenberg, David; Ellis, Andrew; Gebski, Val; Schofield, Peter William (Frontiers in Psychology, 2023)
Background Olfactory deficits have a diverse etiology and can be detected with simple olfactory tests. Key olfactory pathways are located within the frontal and temporal lobes where they are vulnerable to damage due to head trauma. Orbitofrontal cortex (OFC) integrity is important for olfaction and aspects of behavioral regulation. We measured olfactory identification ability in a sample of impulsive violent offenders to determine its associations with history of traumatic brain injury (TBI) and a range of neuropsychiatric indices, including proxies for cognitive ability, impulsivity and social connectedness. Methods Male participants were drawn from the ReINVEST study, a randomized controlled trial of sertraline to reduce recidivism in violent impulsive offenders. Criteria for participation in the study included a minimum age of 18 years, a documented history of two or more violent offenses, and a score of 70 or above on the Barratt Impulsiveness Scale (BIS-11). The 16-item “Sniffin sticks” (SS) odor identification test (OI) was administered as were standardized questionnaires regarding previous TBI, additional measures to screen cognition [word reading test of the Wechsler Individuals Achievement Test (WIAT), social connectedness (the Duke Social Support Scale), and a range of other neuropsychiatric conditions or symptoms]. The sample SS scores were compared against published age-specific norms. Univariate and multivariate analyses were performed with SS score (linear regression, within those without hyposmia) or hyposmia (logistic regression) as the outcome. Results The mean OI scores were lower than population norms and 16% of participants were classified as hyposmic. Univariate analyses showed associations of SS score with age, WIAT score, impulsivity, TBI and TBI severity, social connectedness, childhood sexual abuse, suicidality and current use of heroin. In multivariate analyses, age, TBI severity and WIAT remained as significant independent predictors of SS score (within the normosmic range) or hyposmia (logistic regression). Conclusion Olfactory performance was associated with multiple behavioral phenomena in a pattern that would be consistent with this serving as a proxy for orbitofrontal functioning. As such, OI testing may have utility in further studies of offenders. In future, we will examine whether olfactory score predicts recidivism or response to the administration of sertraline, in terms of reducing recidivism.